THE NEW VISION OF THE EDUCATIONAL AND SCIENTIFIC PROGRAM BY SPECIALTY 224 «TECHNOLOGIES OF MEDICAL DIAGNOSIS AND TREATMENT» - Mintser, O.P.; Babintseva, L. Yu.; Krasnov, V. V.; Korol, P. O.; Shcherbina, O. V.; Kozarenko, T. M.; Sergiienko, L. I. (Medical Informatics and Engineering, 2025)
Background. The modern period of human development is characterized by a significant influence of technologies, in particular information technologies, which ensure the spread of information flows, forming a global information space. They quickly turned into a vital stimulus for the development of not only the world economy, but also other spheres of human activity. Material and methods. The development of the theory and practice of application of technologies of diagnostics and treatment of diseases of internal organs, including informational ones is analyzed by methods of expert assessment. The main task of modern scientific technologies is the implementation of innovative, effective solutions, starting with the everyday life of every person and ending with the implementation of developments in industrial production, health care, the agricultural sector, etc. Results. A modern idea of the training program for future specialists of the degree of Doctor of Philosophy in the specialty 224 “Technologies of medical diagnosis and treatment” (according to the international classification 0914 “Medical diagnostic and treatment technology”) of the branch of knowledge 22 “Health care” is presented. In the field of health care, technology helps improve the quality of health care delivery, improve communication and relationships between health professionals and patients, and certainly provides fast and effective solutions for the diagnosis and treatment of various diseases. The involvement of information and communication and digital technologies, microelectronics is associated with the emergence of digital health care, telemedicine, mobile medicine, etc. It should also be remembered that the decision-making by the doctor about diagnosis, prevention and treatment of the patient depends on the level of reliability of the research. The topics of the training courses are designed to promote the ability to integrate knowledge and solve complex problems in multidisciplinary and transdisciplinary contexts. Conclusion. The content of the proposed educational-scientific program in specialty 224 “Technologies of medical diagnostics and treatment” is aimed at the training of highly qualified and competitive specialists, their acquisition of the necessary theoretical knowledge and a set of practical abilities, skills and competences for the implementation of innovative scientific research and the implementation of the obtained results in practical health care. Based on the goal of improving the quality and efficiency of medical care, modern technologies of clinical laboratory and radiation research methods have been unified; radiation therapy methods, as well as decision-making methods in diagnosis, treatment and prognosis of patient conditions.